CUSTOMER RELATIONSHIP MANAGEMENT, INNOVATION STRATEGY, AND MARKET ORIENTATION ON BUSINESS GROWTH - Abas, Sofyan; Sumantyo, Franciscus Dwikotjo Sri; Adiguna, Patria; Purwoko, Bambang (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study investigates the effects of Customer Relationship Management (CRM), Innovation Strategy, and Market Orientation on Business Growth, including the moderating roles of Innovation Strategy and Market Orientation in strengthening these relationships. Utilizing a quantitative approach, data were collected from mid-sized and large firms across various industries. Structural Equation Modeling (SEM) analysis reveals that CRM, Innovation Strategy, and Market Orientation each have significant positive impacts on business growth. Furthermore, Innovation Strategy and Market Orientation significantly moderate the relationship between CRM and business growth, as well as between Innovation Strategy and business growth, indicating synergistic effects among these variables. The findings suggest that businesses adopting an integrated strategic framework combining CRM, innovation, and market orientation are more likely to achieve sustainable growth. This research provides both theoretical insights and practical implications for managers aiming to enhance firm performance in competitive markets.